A prospective non-interventional study for evaluation of quality of life in patients with Alzheimer’s disease treated with rivastigmine transdermal patch - Vagenas, Vassileios (SAGE Open Med, 2015)
OBJECTIVES: The primary objective of this multicentre, prospective, observational study was to assess whether there is improvement in the patients’ quality of life under treatment with rivastigmine transdermal patch, as it is evaluated both by patients and their caregivers. Compliance to treatment and safety were secondary endpoints. METHODS: In total, 1509 patients with mild to moderate Alzheimer’s disease, already treated with rivastigmine transdermal patch 4.6 or 9.5 mg/24 h, were enrolled within a 2.4-month period and prospectively followed up for 2 months on an outpatient basis. The ‘Quality of Life in Alzheimer’s disease (QOL-AD): Patient and Caregiver Report’ questionnaire was used to evaluate quality of life as an effectiveness measure. RESULTS AND CONCLUSION: A significant improvement in quality of life, as indicated by a change of 2.7 and 2.5 points in the mean patients’ and caregiver’s QOL-AD: Patient and Caregiver Report score respectively (both p < 0.001) from baseline to end of study was recorded. No serious adverse events were reported. Compliance was high, with 100% compliance reported for almost 9 out of 10 patients at study end.